São Tomé and Príncipe: Political Instability Continues - Seibert, Gerhard (2013)
The recent political crisis provoked by the controversial dismissal of Patrice Trovoada’s minority government by a censure motion has again drawn the attention to politics in this small impoverished African island republic that has been marked by political instability since the introduction of a democratic constitution based on the Portuguese semi-presidential regime in 1990. Following the end of Miguel Trovoada’s ten-year presidency in 2001 his son Patrice has become one of the principal political competitors in São Tomé and Príncipe, while his father retired from national politics and, in 2009 has become executive secretary of the Gulf of Guinea Commission.